2017
DOI: 10.1111/irv.12488
|View full text |Cite
|
Sign up to set email alerts
|

National burden of hospitalized and non‐hospitalized influenza‐associated severe acute respiratory illness in Kenya, 2012‐2014

Abstract: BackgroundInfluenza‐associated respiratory illness was substantial during the emergence of the 2009 influenza pandemic. Estimates of influenza burden in the post‐pandemic period are unavailable to guide Kenyan vaccine policy.ObjectivesTo update estimates of hospitalized and non‐hospitalized influenza‐associated severe acute respiratory illness (SARI) during a post‐pandemic period (2012‐2014) and describe the incidence of disease by narrow age categories.MethodsWe used data from Siaya County Referral Hospital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 24 publications
11
64
1
Order By: Relevance
“…In addition, individuals that may have developed influenza‐associated mild or severe illness, but did not seek care would have been missed in our study. A large proportion of nonmedically attended influenza‐associated ILI and SARI has been reported in other studies conducted in Africa; hence, our estimates should be considered minimum estimates. Cultural differences and differential access to healthcare across different countries can also play a role in differential healthcare‐seeking behavior that in return may be responsible for differences in outpatient consultation and hospitalization rates.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, individuals that may have developed influenza‐associated mild or severe illness, but did not seek care would have been missed in our study. A large proportion of nonmedically attended influenza‐associated ILI and SARI has been reported in other studies conducted in Africa; hence, our estimates should be considered minimum estimates. Cultural differences and differential access to healthcare across different countries can also play a role in differential healthcare‐seeking behavior that in return may be responsible for differences in outpatient consultation and hospitalization rates.…”
Section: Discussionmentioning
confidence: 94%
“…Integrated and well-run multi-pathogen surveillance systems, if adequately staffed may provide high quality and timely epidemiological and virological data with a "modest" financial investment. The national burden of illness attributable to specific pathogens can be estimated from sentinel surveillance data through special studies as demonstrated in Zambia and other African countries for influenza [10][11][12][13][14][15][16]. This would be particularly relevant for policy makers if multiple pathogens are included so as to provide the relative burden associated with different etiological agents.…”
Section: Discussionmentioning
confidence: 99%
“…Such evaluations are useful to identify shortfalls, improve performance and provide evidence of data reliability for policy making and public health interventions. However, despite recent progress in describing the epidemiology and burden of influenza in sub-Saharan Africa [8][9][10][11][12][13][14][15][16], only a few countries have implemented a comprehensive evaluation of their surveillance systems [17][18][19][20][21].…”
mentioning
confidence: 99%
“…As such, we do not consider the mortality estimates (6‐11 per 100 000 population) in Bangladesh to be high when compared to other countries; however, we do consider 6‐11 deaths per 100 000 population to be a substantial burden for the country of Bangladesh. Similarly, the estimated influenza‐associated hospitalization rates in Rwanda (34 per 100 000 population) are comparable to those of other African countries situated in equatorial, tropical, and subtropical regions: 21 (95% CI: 19‐23) per 100 000 population in Kenya,8 30 (95% CI: 13‐84) per 100 000 population in Ghana,9 30 (95% CI: 24‐36) per 100 000 population in Madagascar,10 45 (95% CI: 41‐49) per 100 000 population in South Africa,11 and 44 (95% CI: 31‐57) per 100 000 population in Zambia 12. In addition, a global study reported the highest rates of influenza‐associated hospitalization among African children followed by South‐East Asia and the Western Pacific 13.…”
mentioning
confidence: 59%
“…To address this, an analysis exploring the effect of respiratory syncytial virus (RSV) circulation on ARI deaths among children <5 years of age in Bangladesh is underway and similar studies could be conducted in Rwanda. Nonetheless, the estimated influenza‐associated hospitalization rates among children aged <5 years in Rwanda (168 per 100 000 population)3 are similar to those of South Africa (156 per 100 000 population),11 other countries in Africa,8, 9, 12 and global estimates for Africa (174 per 100 000 population) 13. Whereas the circulation patterns of RSV are poorly understood in Rwanda and other African countries, in South Africa, the RSV season precedes and minimally overlaps with the influenza season 24.…”
mentioning
confidence: 80%